Kajian Historis Bimbingan dan Konseling di SMK Negeri 2 Tasikmalaya - Ibnu Hiban; Feida Noorlaila Isti’adah; Refriza Aqila; Zulfa Nadia; Gusti Mujiba Ahsana; Alya Oktaviani; An Nisaa Febrianti; Yuli Amelia (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The historical foundation of guidance and counselling (BK) in Indonesia plays an important role in shaping the practice of BK services in various educational institutions, including at SMK Negeri 2 Tasikmalaya. This study uses a descriptive qualitative approach using interview, observation, and documentation methods aimed at examining the historical foundation and implementation of guidance and counselling (BK) services at SMK Negeri 2 Tasikmalaya, with resource person Mr Abdurrahman, one of the BK teachers. Currently, there are seven counselling teachers handling ±2,600 students with a ratio of 1:150. Each counselling teacher is responsible for one area, including mechanical, automotive, building, electrical, electrical, computer and broadcasting engineering. Observations showed that the school's counselling services include basic, responsive and specialisation services. The main challenges include the lack of counselling teachers, low understanding of the duties of counselling teachers by others, and complex student problems such as smoking. The counselling approach emphasises gradual reduction of negative behaviours and increasing students' trust in the counselling teacher through the principle of credit. The findings indicate the importance of increasing the number of counselling teachers to optimally meet students‘ needs and the need to educate school authorities about the duties and functions of counselling and provide a comprehensive overview of the strategic role of counselling in supporting students’ readiness to face academic and non-academic challenges.